Detection of Novel Gene Mutations Associated with Pyrazinamide Resistance in Multidrug-Resistant Mycobacterium tuberculosis Clinical Isolates in Southern China - Hameed HMA (Infection and Drug Resistance, 2020)
HM Adnan Hameed, 1, 2,* Yaoju Tan, 3,* Md Mahmudul Islam, 1, 2 Zhili Lu, 1 Chiranjibi Chhotaray, 1, 2 Shuai Wang, 1, 2 Zhiyong Liu, 1 Cuiting Fang, 1, 2 Shouyong Tan, 3 Wing Wai Yew, 4 Nanshan Zhong, 5 Jianxiong Liu, 3 Tianyu Zhang 1, 2, 5  1State Key Laboratory of Respiratory Disease, Guangzhou Institutes of Biomedicine and Health (GIBH), Chinese Academy of Sciences (CAS), Guangzhou, People’s Republic of China; 2University of Chinese Academy of Sciences (UCAS), Beijing, People’s Republic of China; 3State Key Laboratory of Respiratory Disease, Guangzhou Chest Hospital, Guangzhou, People’s Republic of China; 4Stanley Ho Centre for Emerging Infectious Diseases, The Chinese University of Hong Kong, Hong Kong, People’s Republic of China; 5National Clinical Research Center for Respiratory Disease, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tianyu ZhangGuangzhou Institutes of Biomedicine and Health (GIBH), Chinese Academy of Sciences (CAS), Room A132, 190 Kaiyuan Ave, Science Park, Huangpu District, Guangzhou 510530, People’s Republic of ChinaTel +86-2032015270Email zhang_tianyu@gibh.ac.cnJianxiong LiuGuangzhou Chest Hospital, 62 Hengzhigang Road, Yuexiu District, Guangzhou 510095, People’s Republic of ChinaTel +86-2083595977Email ljxer64@qq.comObjective: Pyrazinamide (PZA) is a cornerstone of modern tuberculosis regimens. This study aimed to investigate the performance of genotypic testing of pncA+ upstream region, rpsA, panD, Rv2783c, and clpC1 genes to add insights for more accurate molecular diagnosis of PZA-resistant (R) Mycobacterium tuberculosis.Methods: Drug susceptibility testing, sequencing analysis of PZA-related genes including the entire operon of pncA (Rv2044c-pncA-Rv2042c) and PZase assay were performed for 448 M. tuberculosis clinical isolates.Results: Our data showed that among 448 M. tuberculosis clinical isolates, 113 were MDR, 195 pre-XDR and 70 XDR TB, while the remaining 70 strains had other combinations of drug-resistance. A total of 60.04% (269/448) M. tuberculosis clinical isolates were resistant to PZA, of which 78/113 were MDR, 119/195 pre-XDR and 29/70 XDR TB strains. PZAR isolates have predominance (83.3%) of Beijing genotype. Genotypic characterization of Rv2044c-pncA-Rv2042c revealed novel nonsynonymous mutations in Rv2044c with negative PZase activity which led to confer PZAR. Compared with phenotypic data, 84.38% (227/269) PZAR strains with mutations in pncA+ upstream region exhibited 83.64% sensitivity but the combined evaluation of the mutations in rpsA 2.60% (7/269), panD 1.48% (4/269), Rv2783c 1.11% (3/269) and Rv2044c 0.74% (2/269) increased the sensitivity to 89.59%. Fifty-seven novel mutations were identified in this study. Interestingly, a frameshift deletion (C− 114del) in upstream of pncAwt nullified the effect of A− 11G mutation and induced positive PZase activity, divergent from five PZase negative A− 11G PZAR mutants. Twenty-six PZAR strains having wild-type-sequenced genes with positive or negative PZase suggest the existence of unknown resistance mechanisms.Conclusion: Our study revealed that PZAR rate in MDR and pre-XDR TB was markedly higher in southern China. The concomitant evaluation of pncA+ UFR, rpsA, panD, Rv2783c, and Rv2044c provides more dependable genotypic results of PZA resistance. Fifty-seven novel mutations/indels in this study may play a vital role as diagnostic markers. The upstream region of pncA and PZase regulation are valuable to explore the unknown mechanism of PZA-resistance.Keywords: tuberculosis, pyrazinamidase, drug resistance, molecular diagnosis, novel mutations, frameshift deletion